Preparation method of MABS resin

Through the combined process of a multi-stage piston flow reactor and a static mixing reactor, the polymerization process and the rubber particle distribution are optimized, which solves the preparation problem of MABS resin in traditional processes, and achieves efficient and uniform rubber particle distribution and excellent optical and mechanical properties.

CN119638900APending Publication Date: 2025-03-18DALIAN UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411562918.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The preparation of MABS resins in traditional continuous body method has problems such as difficulty in polymerization heat dissipation, difficulty in controlling the size and distribution of rubber particles, low monomer conversion rate, and difficult to balance optical and mechanical properties.

Method used

The combined process of multi-stage piston flow reactor and static mixing reactor is adopted to accurately adjust the morphological structure and size distribution of rubber particles by optimizing external conditions and viscosity control during the polymerization process, improve grafting rate and transparency, reduce haze and improve impact resistance.

Benefits of technology

The obtained MABS resin product is pure, has a low odor, uniform distribution of rubber particles, high graft rate, good transparency, low haze and good impact resistance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer material synthesis and preparation, and particularly relates to a preparation method of MABS (methyl acrylonitrile butadiene styrene) resin, which comprises the following steps: by taking styrene, acrylate monomers, acrylonitrile and toughened rubber particles as raw materials, under the combined action of an antioxidant, an initiator and a chain transfer agent, optimizing the technical process and adjusting the technical parameters, thereby obtaining the MABS resin. Three-stage key process steps of internal circulation prepolymerization, three-stage reactor polymerization and grafting in a static mixer are set, and by accurately controlling the feeding proportion of reaction materials, catalytic materials and the like and the reaction temperature, the stirring speed, the retention time, the solid content proportion and the like of each process step, the high-temperature-resistant and high-temperature-resistant polymer is obtained. The prepared MABS resin product is pure, low in odor, uniform in rubber particle distribution, high in grafting rate, good in transparency, low in haze and good in impact resistance, and has good market prospects and application and popularization values.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer material synthesis and preparation technology, and specifically relates to a preparation method of MABS resin. Background Art

[0002] MABS is a transparent resin obtained by copolymerization of acrylonitrile (AN), styrene (St), methyl methacrylate (MMA) and butadiene (BD), also known as transparent ABS. Compared with ordinary ABS, MABS adjusts the refractive index of the resin by introducing MMA monomer to make the refractive index of each component tend to be uniform, thereby obtaining transparency. MABS resin is a high-strength plastic that combines the mechanical properties and transparency of ordinary ABS resin. It can be used to manufacture some important components, such as optical disks, optical fibers, light-emitting diodes and other transparent material products. MABS is also widely used in various top covers, shells and containers, toys, decorations, industrial packaging, automotive parts, syringes and transparent power tools. In addition, since its products can be electroplated, hot-dip plated and vacuum metallized, it can also replace certain metal parts and plastic parts. Therefore, it has a very broad application prospect in electrical appliances, instruments, automobiles, medical equipment and electronic industries.

[0003] The production process of MABS is mainly emulsion grafting and blending and bulk polymerization. The main process of emulsion grafting and blending includes the synthesis of grafting backbone latex, grafting copolymerization of backbone latex with styrene and acrylonitrile, synthesis of SAN copolymer and blending of ABS graft copolymer with SAN resin. Methyl methacrylate participates in the polymerization in the grafting copolymerization of backbone latex with styrene and acrylonitrile or the synthesis of SAN copolymer. The continuous bulk polymerization method is to dissolve a certain amount of toughened rubber in methyl methacrylate, styrene and acrylonitrile monomers prepared in proportion, and continuously add them to a fully mixed flow reactor in the presence of a small amount of solvent to achieve phase transition, and then continue to react through a multi-stage plug flow reactor. The whole polymerization process is also accompanied by grafting reaction. Then, after the material reaches a certain conversion rate, it is sent to the devolatilizer to flash out the unreacted methyl methacrylate, styrene and acrylonitrile monomers and solvent and recycle them. The molten material is then granulated to obtain the MABS resin product. The continuous bulk method has the advantages of simple equipment, short process and environmental protection. The preparation of MABS resin by the continuous bulk method is an important research direction in the industry.

[0004] For the preparation of MABS resin by bulk polymerization, the amount of rubber significantly increases the viscosity of the post-sol system, and has a more prominent impact on the polymerization phase transition process and the performance of the product. Bulk transparent MABS resin consists of a rubber phase and a resin phase. Generally, good optical properties are obtained by adjusting the refractive index of the two phases and controlling the morphological structure and size distribution of the rubber particles. However, the disadvantages of the traditional continuous bulk method for preparing MABS are that polymerization heat dissipation is difficult, the size, particle size distribution and morphology of the rubber particles are difficult to control, and the monomer conversion rate is low. In addition, the biggest difficulty in the production of bulk transparent MABS resin is that it is difficult to balance the optical properties and mechanical properties. While improving transparency, the haze is high and the impact strength is reduced, which greatly limits its scope of application. Summary of the invention

[0005] Based on the above problems, the present invention develops a method for preparing MABS resin. The MABS resin product obtained by the preparation method of the present invention is pure, has low product odor, uniform distribution of rubber particles, high grafting rate, good transparency, low haze, and good impact resistance.

[0006] A method for preparing MABS resin comprises the following steps:

[0007] S1. Preparation of reaction materials: prepare a mixed solution of styrene, acrylate monomer, acrylonitrile, toughened rubber particles, solvent and antioxidant in proportion, add initiator and chain transfer agent to the mixed solution, stir well to ensure that the toughened rubber particles are completely dissolved; place the mixed solution in a three-stage static mixer for prepolymerization, the reaction temperature is between 100-110° C., the stirring speed is 10-25 r / min, the prepolymerization residence time is 0.5-1.0 hour, and the solid content at the outlet is controlled at 12-15%;

[0008] S2, pumping the prepolymerized mixture from step S1 into a primary plug flow reactor, controlling the reaction temperature to 100-110°C, the stirring speed to 15-30r / min, the residence time to 1.0-1.5 hours, and the solid content of the material at the outlet to 40%-45%;

[0009] S3, the mixed material is pumped from the primary plug flow reactor to the secondary plug flow reactor, the reaction temperature is controlled at 110-120°C, the stirring speed is 5-12r / min; the material residence time is 1.5-2.0 hours, and the solid content of the material at the outlet is 55%-60%;

[0010] S4, the mixed material is pumped from the secondary plug flow reactor to the tertiary plug flow reactor, the reaction temperature is controlled at 120-130°C, the stirring speed is 2-5r / min; the material residence time is 2.0-2.5 hours, and the solid content of the material at the outlet is 70%-75%;

[0011] S5, the material is pumped from the three-stage plug flow reactor to a static mixing reactor, the temperature of the upper and middle zones of the static mixing reactor is controlled to be 90-100°C, and the reaction temperature of the lower zone is controlled to be 130-150°C; the material residence time is 1.0-2.0 hours, and the solid content of the material at the outlet is 80%-85%; after the material reaches the conversion rate, it is subjected to secondary deashing treatment, and the volatile content at the outlet is controlled to be no more than 300ppm, and granulation is performed to obtain the MABS resin finished product.

[0012] Furthermore, the toughening rubber is selected from at least one of styrene-butadiene copolymer rubber, styrene-isoprene-butadiene ternary integrated rubber, amine-functionalized styrene-butadiene copolymer rubber, and amine-functionalized styrene-isoprene-butadiene copolymer integrated rubber; preferably styrene-butadiene copolymer rubber.

[0013] Furthermore, the solvent is toluene or ethylbenzene.

[0014] Furthermore, the initiator is not particularly limited and can be used alone or in combination. The initiator is selected from one or more of 2,2'-azobisisobutyronitrile, dilauroyl peroxide, and dibenzoyl peroxide.

[0015] Furthermore, the chain transfer agent is selected from chain transfer agents commonly used in free radical polymerization, including but not limited to at least one of n-butyl mercaptan, isobutyl mercaptan, n-dodecyl mercaptan, and tert-dodecyl mercaptan, preferably n-dodecyl mercaptan;

[0016] The antioxidant is not particularly limited and can be used alone or in combination, preferably 1-octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate;

[0017] Furthermore, in terms of mass fraction, the toughened rubber accounts for 6%-12% of the total amount of the mixed glue including styrene, acrylate monomers, acrylonitrile, initiator, chain transfer agent and solvent, the amount of styrene accounts for 25%-45% of the total amount of the mixed glue, the amount of solvent accounts for 10%-20% of the total amount of the mixed glue, the acrylate monomers account for 15%-25% of the total amount of the mixed glue, and acrylonitrile accounts for 18%-25% of the total amount of the mixed glue; the amount of initiator is 0.05-0.2% of the total mass of the reaction monomers; the amount of chain transfer agent is 0.10%-0.40% of the total mass of the acrylate monomers, styrene and acrylonitrile; the amount of antioxidant is 0.10%-0.3% of the total mass of the acrylate monomers, styrene and acrylonitrile.

[0018] Furthermore, the acrylic acid ester monomer used for polymerization is selected from methyl methacrylate, ethyl methacrylate, and butyl methacrylate, preferably methyl methacrylate.

[0019] Beneficial effects:

[0020] 1. The present invention adopts a bulk polymerization method to prepare a transparent MABS resin. The preparation process adopted can accurately control the morphological structure and size distribution of rubber particles, optimize the phase inversion process, and improve the monomer conversion rate. The MABS resin product obtained by the preparation method is pure, has low product odor, uniform distribution of rubber particles, high grafting rate, good transparency, low haze, and good impact resistance.

[0021] 2. From the perspective of reaction mechanism, in the process of resin phase formation, volume enlargement, and graft copolymerization, the optimization measures include: 1) Optimizing the shear force of external conditions acting on the system during the polymerization process, that is, the process of mechanical stirring; 2) Accurately controlling the viscosity of each part of the system, including the viscosity of the rubber itself, the viscosity of the rubber phase and the resin phase, and their viscosity ratio during the reaction process; 3) Optimizing the grafting process, which includes internal grafting and external grafting. The difference in the amount of internal and external grafting will affect the size, distribution, and internal inclusion structure of the rubber particles. This can be used as a means to effectively control the phase structure of the bulk MABS resin, and then regulate the macroscopic properties. DETAILED DESCRIPTION

[0022] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0023] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.

[0024] The preferred embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that the following examples are provided only for the purpose of illustration and are not intended to limit the scope of the present invention. Those skilled in the art may make various modifications and substitutions to the present invention without departing from the purpose and spirit of the present invention.

[0025] Test instrument model:

[0026] The rubber content was measured by nuclear magnetic resonance spectroscopy (NMR);

[0027] The grafting rate was measured by differential weight method: about 0.15g of MABS sample (W 样) was dissolved in 30 mL of acetone solvent, refluxed for 8 h, centrifuged at 6000 rpm on an ultracentrifuge for 30 min, the supernatant was transferred to a watch glass, condensed with ethanol, and reserved for molecular weight and distribution measurement. The lower precipitate was repeatedly washed with solvent, and this was repeated, centrifuged 3 times, and dried at 50 ° C under vacuum to constant weight (W 沉淀 ).

[0028] Grafting rate = (W 沉淀 -W 橡胶 ) / W 橡胶 ×100%

[0029] Transparency and haze were measured using a photometric haze meter;

[0030] Impact resistance is measured using an impact tester.

[0031] Example 1

[0032] S1. Preparation of reaction materials: prepare a mixed solution of styrene, methyl methacrylate, acrylonitrile, toughened rubber particles, toluene and antioxidant in proportion, add initiator and chain transfer agent to the mixed solution, stir well to ensure that the toughened rubber particles are completely dissolved; place the reaction materials in a three-stage static mixer in turn for prepolymerization, the reaction temperature is 100° C., the stirring speed is 25 r / min, the prepolymerization residence time is 1.0 hour, and the solid content at the outlet is controlled at 12%-15%;

[0033] S2, pump the prepolymerized material from the inner circulation reactor into the primary plug flow reactor, control the reaction temperature at 100°C, the stirring speed at 30r / min, the residence time at 1.5 hours, and the solid content of the material at the outlet at 40%-45%;

[0034] S3, the material is pumped from the primary plug flow reactor to the secondary plug flow reactor, the reaction temperature is controlled at 110°C, the stirring speed is 12r / min; the material residence time is 2.0 hours, and the solid content of the material at the outlet is 55%-60%;

[0035] S4, the material is pumped from the secondary plug flow reactor to the tertiary plug flow reactor, the reaction temperature is controlled at 120°C, the stirring speed is 5r / min; the material residence time is 2.5 hours, and the solid content of the material at the outlet is 70%-75%;

[0036] S5, the material is pumped from the three-stage plug flow reactor to a static mixing reactor, the temperature of the upper and middle zones of the static mixing reactor is controlled to be 90°C, and the reaction temperature of the lower zone is controlled to be 130°C; the material residence time is 2.0 hours, and the solid content of the material at the outlet is 80%-85%; after the material reaches the conversion rate, it is subjected to secondary deashing treatment, and the volatile content at the outlet is controlled to be less than 300ppm, and granulation is performed to obtain the MABS resin finished product.

[0037] The toughening rubber is selected from styrene-butadiene copolymer rubber; the initiator is 2,2'-azobisisobutyronitrile; the chain transfer agent is n-butyl mercaptan; and the antioxidant is selected from 1-octadecyl-3-(3.5-di-tert-butyl-4-hydroxyphenyl) propionate.

[0038] The toughened rubber accounts for 9% of the weight ratio of the mixed glue liquid including styrene, methyl methacrylate, acrylonitrile, initiator, chain transfer agent and solvent, styrene accounts for 36% of the total amount of the glue liquid, the solvent accounts for 15% of the total amount of the glue liquid, methyl methacrylate accounts for 20% of the total amount of the glue liquid, and acrylonitrile accounts for 20% of the total amount of the glue liquid; the amount of initiator used is 0.1% of the total mass of the monomers; the amount of chain transfer agent used is 0.1% of the sum of the mass of methyl methacrylate, styrene and acrylonitrile; the amount of antioxidant used is 0.3% of the total mass of methyl methacrylate, styrene and acrylonitrile.

[0039] The prepared MABS resin product is pure, has low odor, and has uniformly distributed rubber particles; the rubber grafting rate is 279%, the light transmittance is 90%, the haze is 6%, and the cantilever beam impact strength is 181 J / m.

[0040] Example 2

[0041] S1. Preparation of reaction materials: prepare a mixed solution of styrene, methyl methacrylate, acrylonitrile, toughened rubber particles, ethylbenzene and antioxidant in proportion, add initiator and chain transfer agent to the mixed solution, stir well to ensure that the toughened rubber particles are completely dissolved; place the reaction materials in a three-stage static mixer for prepolymerization, the reaction temperature is between 110° C., the stirring speed is 10 r / min, the prepolymerization residence time is 0.5 hour, and the solid content at the outlet is controlled at 12-15%;

[0042] S2, pump the prepolymerized material from the inner circulation reactor into the primary plug flow reactor, control the reaction temperature to 110°C, the stirring speed to 15r / min, the residence time to 1.0 hour, and the solid content of the material at the outlet to 40-45%;

[0043] S3, the material is pumped from the primary plug flow reactor to the secondary plug flow reactor, the reaction temperature is controlled at 120°C, the stirring speed is 5r / min; the material residence time is 1.5 hours, and the solid content of the material at the outlet is 55-60%;

[0044] S4, the material is pumped from the secondary plug flow reactor to the tertiary plug flow reactor, the reaction temperature is controlled at 130°C, the stirring speed is 2r / min; the material residence time is 2.0 hours, and the solid content of the material at the outlet is 70-75%;

[0045] S5, the material is pumped from the three-stage plug flow reactor to a static mixing reactor, the temperature of the upper and middle zones of the static mixing reactor is controlled to be 100°C, and the reaction temperature of the lower zone is controlled to be 150°C; the material residence time is 1.0 hour, and the solid content of the material at the outlet is 80-85%; after the material reaches the conversion rate, it is subjected to secondary deashing treatment, and the volatile content at the outlet is controlled to be less than 300ppm, and granulation is performed to obtain the MABS resin finished product.

[0046] The toughening rubber is selected from styrene-isoprene-butadiene ternary integrated rubber; the initiator is dilauroyl peroxide; the chain transfer agent is isobutyl mercaptan, and the antioxidant is selected from 1-octadecyl-3-(3.5-di-tert-butyl-4-hydroxyphenyl) propionate.

[0047] The toughened rubber accounts for 12% of the weight ratio of the mixed glue liquid including styrene, methyl methacrylate, acrylonitrile, initiator, chain transfer agent and solvent, styrene monomer accounts for 45% of the total amount of the glue liquid, the solvent accounts for 10% of the total amount of the glue liquid, methyl methacrylate accounts for 15% of the total amount of the glue liquid, and acrylonitrile accounts for 18% of the total amount of the glue liquid; the amount of initiator used is 0.2% of the total weight of the monomers; the amount of chain transfer agent used is 0.4% of the total weight of acrylate monomers, styrene monomers and acrylonitrile; the amount of antioxidant used is 0.1% of the total weight of acrylate monomers, styrene monomers and acrylonitrile.

[0048] The prepared MABS resin product is pure, has low odor, and has uniformly distributed rubber particles; wherein the rubber grafting rate is 258%, the transparency is 89%, the haze is 7%, and the impact resistance is 177 J / m.

[0049] Example 3

[0050] S1. Preparation of reaction materials: prepare a mixed solution of styrene, ethyl methacrylate, acrylonitrile, toughened rubber particles, ethylbenzene and antioxidant in proportion, add initiator and chain transfer agent to the mixed solution, stir well to ensure that the toughened rubber particles are completely dissolved; place the reaction materials in a three-stage static mixer for prepolymerization, the reaction temperature is 110° C., the stirring speed is 10 r / min, the prepolymerization residence time is 0.5 hour, and the solid content at the outlet is controlled at 12-15%;

[0051] S2, pump the prepolymerized material from the inner circulation reactor into the primary plug flow reactor, control the reaction temperature to 110°C, the stirring speed to 15r / min, the residence time to 1.0 hour, and the solid content of the material at the outlet to 40-45%;

[0052] S3, the material is pumped from the primary plug flow reactor to the secondary plug flow reactor, the reaction temperature is controlled at 120°C, the stirring speed is 5r / min; the material residence time is 1.5 hours, and the solid content of the material at the outlet is 55-60%;

[0053] S4, the material is pumped from the secondary plug flow reactor to the tertiary plug flow reactor, the reaction temperature is controlled at 130°C, the stirring speed is 2r / min; the material residence time is 2.0 hours, and the solid content of the material at the outlet is 70-75%;

[0054] S5, the material is pumped from the three-stage plug flow reactor to a static mixing reactor, the temperature of the upper and middle zones of the static mixing reactor is controlled to be 100°C, and the reaction temperature of the lower zone is controlled to be 150°C; the material residence time is 2.0 hours, and the solid content of the material at the outlet is 80-85%; after the material reaches the conversion rate, it is subjected to secondary deashing treatment, and the volatile content at the outlet is controlled to be less than 300ppm, and granulation is performed to obtain the MABS resin finished product.

[0055] The toughening rubber is selected from styrene-isoprene-butadiene ternary integrated rubber; the initiator is dibenzoyl peroxide; the chain transfer agent is n-dodecyl mercaptan, and the antioxidant is selected from 1-octadecyl-3-(3.5-di-tert-butyl-4-hydroxyphenyl) propionate.

[0056] The toughened rubber accounts for 12% of the weight ratio of the mixed glue liquid including styrene, ethyl methacrylate, acrylonitrile, initiator, chain transfer agent and solvent, styrene monomer accounts for 25% of the total amount of the glue liquid, the solvent accounts for 20% of the total amount of the glue liquid, ethyl methacrylate accounts for 25% of the total amount of the glue liquid, and acrylonitrile accounts for 18% of the total amount of the glue liquid; the amount of initiator used is 0.05% of the total weight of the monomers; the amount of chain transfer agent used is 0.3% of the total weight of acrylate monomers, styrene monomers and acrylonitrile; the amount of antioxidant used is 0.2% of the total weight of acrylate monomers, styrene monomers and acrylonitrile.

[0057] The prepared MABS resin product is pure, has low odor, and has uniformly distributed rubber particles; wherein the rubber grafting rate is 197%, the transparency is 88%, the haze is 9%, and the impact resistance is 158 J / m.

[0058] Example 4

[0059] S1. Preparation of reaction materials: prepare a mixed solution of styrene, butyl methacrylate, acrylonitrile, toughened rubber particles, ethylbenzene and antioxidant in proportion, add initiator and chain transfer agent to the mixed solution, stir well to ensure that the toughened rubber particles are completely dissolved; place the reaction materials in a three-stage static mixer for prepolymerization, the reaction temperature is 110° C., the stirring speed is 15 r / min, the prepolymerization residence time is 0.8 hours, and the solid content at the outlet is controlled at 12-15%;

[0060] S2, pump the prepolymerized material from the inner circulation reactor into the primary plug flow reactor, control the reaction temperature at 100°C, the stirring speed at 25r / min, the residence time at 1.2 hours, and the solid content of the material at the outlet at 40-45%;

[0061] S3, the material is pumped from the primary plug flow reactor to the secondary plug flow reactor, the reaction temperature is controlled at 110°C, the stirring speed is 6r / min; the material residence time is 1.7 hours, and the solid content of the material at the outlet is 55-60%;

[0062] S4, the material is pumped from the secondary plug flow reactor to the tertiary plug flow reactor, the reaction temperature is controlled at 120°C, the stirring speed is 5r / min; the material residence time is 2.0 hours, and the solid content of the material at the outlet is 70-75%;

[0063] S5, the material is pumped from the three-stage plug flow reactor to a static mixing reactor, the temperature of the upper and middle zones of the static mixing reactor is controlled to be 100°C, and the reaction temperature of the lower zone is controlled to be 150°C; the material residence time is 2.0 hours, and the solid content of the material at the outlet is 80-85%; after the material reaches the conversion rate, it is subjected to secondary deashing treatment, and the volatile content at the outlet is controlled to be less than 300ppm, and granulation is performed to obtain the MABS resin finished product.

[0064] The toughening rubber is selected from terminal amine functionalized styrene-butadiene copolymer rubber; the initiator is dilauroyl peroxide; the chain transfer agent is n-dodecyl mercaptan, and the antioxidant is selected from 1-octadecyl-3-(3.5-di-tert-butyl-4-hydroxyphenyl) propionate.

[0065] The toughened rubber accounts for 6% of the weight ratio of the mixed glue liquid including styrene, butyl methacrylate, acrylonitrile, initiator, chain transfer agent and solvent, styrene monomer accounts for 32% of the total amount of the glue liquid, the solvent accounts for 12% of the total amount of the glue liquid, butyl methacrylate accounts for 25% of the total amount of the glue liquid, and acrylonitrile accounts for 25% of the total amount of the glue liquid; the amount of initiator used is 0.1% of the total weight of the monomers; the amount of chain transfer agent used is 0.2% of the total weight of acrylate monomers, styrene monomers and acrylonitrile; the amount of antioxidant used is 0.2% of the total weight of acrylate monomers, styrene monomers and acrylonitrile.

[0066] The prepared MABS resin product is pure, has low odor, and has uniformly distributed rubber particles; wherein the rubber grafting rate is 249%, the transparency is 85%, the haze is 10%, and the impact resistance is 154 J / m.

[0067] Comparative Example 1

[0068] S1. Preparation of reaction materials: prepare a mixed solution of styrene, acrylonitrile, toughened rubber particles, ethylbenzene and antioxidant in proportion, add initiator and chain transfer agent to the mixed solution, stir well to ensure that the toughened rubber particles are completely dissolved; place the reaction materials in a three-stage static mixer in turn for prepolymerization, the reaction temperature is 100° C., the stirring speed is 25 r / min, the prepolymerization residence time is 1.0 hour, and the solid content at the outlet is controlled at 12%-15%;

[0069] S2, pump the prepolymerized material from the inner circulation reactor into the primary plug flow reactor, control the reaction temperature at 100°C, the stirring speed at 30r / min, the residence time at 1.5 hours, and the solid content of the material at the outlet at 40%-45%;

[0070] S3, the material is pumped from the primary plug flow reactor to the secondary plug flow reactor, the reaction temperature is controlled at 110°C, the stirring speed is 12r / min; the material residence time is 2.0 hours, and the solid content of the material at the outlet is 55%-60%;

[0071] S4, the material is pumped from the secondary plug flow reactor to the tertiary plug flow reactor, the reaction temperature is controlled at 120°C, the stirring speed is 5r / min; the material residence time is 2.5 hours, and the solid content of the material at the outlet is 70%-75%;

[0072] S5, the material is pumped from the three-stage plug flow reactor to a static mixing reactor, the temperature of the upper and middle zones of the static mixing reactor is controlled to be 90°C, and the reaction temperature of the lower zone is controlled to be 130°C; the material residence time is 2.0 hours, and the solid content of the material at the outlet is 80%-85%; after the material reaches the conversion rate, it is subjected to secondary deashing treatment, and the volatile content at the outlet is controlled to be less than 300ppm, and granulation is performed to obtain the MABS resin finished product.

[0073] The toughening rubber is selected from styrene-butadiene copolymer rubber; the initiator is 2,2'-azobisisobutyronitrile; the chain transfer agent is n-butyl mercaptan; and the antioxidant is selected from 1-octadecyl-3-(3.5-di-tert-butyl-4-hydroxyphenyl) propionate.

[0074] The toughened rubber accounts for 9% of the weight ratio of the mixed glue liquid including styrene, acrylonitrile, initiator, chain transfer agent and solvent, styrene accounts for 46% of the total amount of the glue liquid, the solvent accounts for 15% of the total amount of the glue liquid, and acrylonitrile accounts for 30% of the total amount of the glue liquid; the amount of initiator is 0.1% of the total weight of the monomers; the amount of chain transfer agent is 0.1% of the sum of the weight of acrylic ester monomers, styrene monomers and acrylonitrile; the amount of antioxidant is 0.3% of the total weight of acrylic ester monomers, styrene monomers and acrylonitrile.

[0075] The prepared MABS resin product is pure, has low odor, and has uniformly distributed rubber particles; wherein the rubber grafting rate is 224%, it is opaque, and has a cantilever beam impact strength of 178 J / m.

[0076] Comparative Example 2

[0077] S1. Preparation of reaction materials: prepare a mixed solution of styrene, butyl methacrylate, acrylonitrile, toughened rubber particles, ethylbenzene and antioxidant in proportion, add initiator and chain transfer agent to the mixed solution, stir well to ensure that the toughened rubber particles are completely dissolved; place the reaction materials in a three-stage static mixer for prepolymerization, the reaction temperature is 110° C., the stirring speed is 15 r / min, the prepolymerization residence time is 0.8 hours, and the solid content at the outlet is controlled at 12-15%;

[0078] S2, pump the prepolymerized material from the inner circulation reactor into the primary plug flow reactor, control the reaction temperature to 110°C, the stirring speed to 25r / min, the residence time to 1.2 hours, and the solid content of the material at the outlet to 40-45%;

[0079] S3, the material is pumped from the primary plug flow reactor to the secondary plug flow reactor, the reaction temperature is controlled at 120°C, the stirring speed is 6r / min; the material residence time is 1.7 hours, and the solid content of the material at the outlet is 55-60%;

[0080] S4, the material is pumped from the secondary plug flow reactor to the tertiary plug flow reactor, the reaction temperature is controlled at 130°C, the stirring speed is 5r / min; the material residence time is 2.0 hours, and the solid content of the material at the outlet is 70-75%;

[0081] S5, the material is pumped from the three-stage plug flow reactor to a static mixing reactor, the temperature of the upper and middle zones of the static mixing reactor is controlled to be 100°C, and the reaction temperature of the lower zone is controlled to be 150°C; the material residence time is 2.0 hours, and the solid content of the material at the outlet is 80-85%; after the material reaches the conversion rate, it is subjected to secondary deashing treatment, and the volatile content at the outlet is controlled to be less than 300ppm, and granulation is performed to obtain the MABS resin finished product.

[0082] The toughening rubber is selected from silane-functionalized styrene-isoprene-butadiene copolymer integrated rubber; the initiator is dilauroyl peroxide; the chain transfer agent is n-dodecyl mercaptan, and the antioxidant is selected from 1-octadecyl-3-(3.5-di-tert-butyl-4-hydroxyphenyl) propionate.

[0083] The toughened rubber accounts for 6% of the weight ratio of the mixed glue liquid including styrene, butyl methacrylate, acrylonitrile, initiator, chain transfer agent and solvent, styrene monomer accounts for 32% of the total amount of the glue liquid, the solvent accounts for 12% of the total amount of the glue liquid, acrylate monomers account for 25% of the total amount of the glue liquid, and acrylonitrile accounts for 25% of the total amount of the glue liquid; the amount of initiator used is 0.15% of the total weight of the monomers; the amount of chain transfer agent used is 0.2% of the total weight of acrylate monomers, styrene monomers and acrylonitrile; the amount of antioxidant used is 0.2% of the total weight of acrylate monomers, styrene monomers and acrylonitrile.

[0084] The prepared MABS resin product is pure, has low odor, and has uniformly distributed rubber particles; among them, the rubber grafting rate is 157%, the transparency is 80%, the haze is 16%, and the impact resistance is 159 J / m.

[0085] Comparative Example 3

[0086] S1. Preparation of reaction materials: prepare a mixed solution of styrene, butyl methacrylate, acrylonitrile, toughened rubber particles, ethylbenzene and antioxidant in proportion, add initiator and chain transfer agent to the mixed solution, stir well to ensure that the toughened rubber particles are completely dissolved; place the reaction materials in a three-stage static mixer for prepolymerization, the reaction temperature is 110° C., the stirring speed is 15 r / min, the prepolymerization residence time is 0.8 hours, and the solid content at the outlet is controlled at 12-15%;

[0087] S2, pump the prepolymerized material from the inner circulation reactor into the primary plug flow reactor, control the reaction temperature to 110°C, the stirring speed to 25r / min, the residence time to 1.2 hours, and the solid content of the material at the outlet to 40-45%;

[0088] S3, the material is pumped from the primary plug flow reactor to the secondary plug flow reactor, the reaction temperature is controlled at 120°C, the stirring speed is 6r / min; the material residence time is 1.7 hours, and the solid content of the material at the outlet is 55-60%;

[0089] S4, the material is pumped from the secondary plug flow reactor to the tertiary plug flow reactor, the reaction temperature is controlled at 130°C, the stirring speed is 5r / min; the material residence time is 2.0 hours, and the solid content of the material at the outlet is 70-75%;

[0090] S5, the material is pumped from the three-stage plug flow reactor to a static mixing reactor, the temperature of the upper and middle zones of the static mixing reactor is controlled to be 100°C, and the reaction temperature of the lower zone is controlled to be 150°C; the material residence time is 2.0 hours, and the solid content of the material at the outlet is 80-85%; after the material reaches the conversion rate, it is subjected to secondary deashing treatment, and the volatile content at the outlet is controlled to be less than 300ppm, and granulation is performed to obtain the MABS resin finished product.

[0091] The toughening rubber is selected from terminal amine functionalized styrene-butadiene copolymer rubber; the initiator is dilauroyl peroxide; the chain transfer agent is n-dodecyl mercaptan, and the antioxidant is selected from 1-octadecyl-3-(3.5-di-tert-butyl-4-hydroxyphenyl) propionate.

[0092] The toughened rubber accounts for 15% of the weight ratio of the mixed glue liquid including styrene, butyl methacrylate, acrylonitrile, initiator, chain transfer agent and solvent, styrene monomer accounts for 32% of the total amount of the glue liquid, the solvent accounts for 12% of the total amount of the glue liquid, butyl methacrylate accounts for 20% of the total amount of the glue liquid, and acrylonitrile accounts for 21% of the total amount of the glue liquid; the amount of initiator used is 0.1% of the total weight of the monomers; the amount of chain transfer agent used is 0.2% of the total weight of acrylate monomers, styrene monomers and acrylonitrile; the amount of antioxidant used is 0.2% of the total weight of acrylate monomers, styrene monomers and acrylonitrile.

[0093] The prepared MABS resin product is pure, has low odor, and has uniformly distributed rubber particles; wherein the rubber grafting rate is 139%, the transparency is 77%, the haze is 25%, and the impact resistance is 255 J / m.

[0094] The above are only preferred embodiments of the present invention, and the protection scope of the present invention is not limited thereto. Any equivalent structure or equivalent process transformation made by using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the protection scope of the present invention.

Claims

1. A method for preparing MABS resin, characterized in that: The following steps are involved: S1. Preparation of reaction materials: prepare a mixed solution of styrene, acrylate monomer, acrylonitrile, toughened rubber particles and antioxidant in proportion, add initiator and chain transfer agent into the mixed solution, stir well to ensure that the toughened rubber particles are completely dissolved; place the mixed solution in a three-stage static mixer for prepolymerization, the reaction temperature is between 100-110° C., the prepolymerization residence time is 0.5-1.0 hour, and the solid content at the outlet is controlled at 12%-15%; S2, pumping the prepolymerized mixture from step S1 into a primary plug flow reactor, controlling the reaction temperature to 100-110°C, the stirring speed to 15-30r / min, the residence time to 1.0-1.5 hours, and the solid content of the material at the outlet to 40%-45%; S3, pumping the mixed material from the primary plug flow reactor into the secondary plug flow reactor, controlling the reaction temperature to 110-120° C. and the stirring speed to 5-12 r / min; The material residence time is 1.5-2.0 hours, and the solid content of the material at the outlet is 55%-60%; S4, pumping the mixed material from the secondary plug flow reactor to the tertiary plug flow reactor, controlling the reaction temperature to 120-130° C. and the stirring speed to 2-5 r / min; The material residence time is 2.0-2.5 hours, and the solid content of the material at the outlet is 70%-75%; S5, pumping the mixed material from the three-stage plug flow reactor to a static mixing reactor, controlling the temperature of the upper and middle zones of the static mixing reactor to 90-100°C, and controlling the reaction temperature of the lower zone to 130-150°C; the material residence time is 1.0-2.0 hours, and the solid content of the material at the outlet is 80%-85%; after the material reaches the conversion rate, it is subjected to secondary deashing treatment, and the volatile content at the outlet is controlled to be less than 300ppm, and granulation is performed to obtain the MABS resin finished product.

2. The preparation method according to claim 1, characterized in that: The toughening rubber is selected from at least one of styrene-butadiene binary copolymer rubber, styrene-isoprene-butadiene ternary integrated rubber, amine-functionalized styrene-butadiene copolymer rubber, and amine-functionalized styrene-isoprene-butadiene copolymer integrated rubber.

3. The preparation method according to claim 1, characterized in that: The acrylic acid ester monomer is selected from methyl methacrylate, ethyl methacrylate and butyl methacrylate.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In terms of mass fraction, the toughened rubber accounts for 6%-12% of the total amount of the mixed adhesive including styrene, acrylate monomers, acrylonitrile, initiator, chain transfer agent and solvent, the styrene accounts for 25%-45% of the total amount of the mixed adhesive, the solvent accounts for 10%-20% of the total amount of the mixed adhesive, the acrylate monomer accounts for 15%-25% of the total amount of the mixed adhesive, and the acrylonitrile accounts for 15%-25% of the total amount of the mixed adhesive; the chain transfer agent is 0.10%-0.40% of the sum of the mass of the acrylate monomers, styrene monomers and acrylonitrile; the initiator is 0.05-0.2% of the total mass of the reaction monomers; the antioxidant is 0.1%-0.3% of the total mass of the acrylate monomers, styrene and acrylonitrile.

5. The preparation method according to claim 4, characterized in that: The initiator is selected from at least one of 2,2'-azobisisobutyronitrile, dilauroyl peroxide and dibenzoyl peroxide.

6. The preparation method according to claim 4, characterized in that: The chain transfer agent is selected from at least one of n-butyl mercaptan, isobutyl mercaptan, n-dodecyl mercaptan and tert-dodecyl mercaptan.

7. The preparation method according to claim 4, characterized in that: The antioxidant is selected from 1-octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate.

8. The preparation method according to claim 4, characterized in that: The solvent is toluene or ethylbenzene.

Citation Information

Patent Citations

  • ABS production technology through bulk polymerization method

    CN103450404A

  • Method of preparing transparent ABS resin by adopting continuous body device

    CN106699981A

  • Preparation method of bimodal-structure high-flow transparent MABS resin

    CN113121757A

  • ABS (Acrylonitrile Butadiene Styrene) resin production process system containing internal circulation device and preparation method thereof

    CN114870781A

  • Production process system and preparation method of high-performance ABS (Acrylonitrile Butadiene Styrene) resin

    CN115057972A